50 géants de l'art Américain : comment New York a détrôné l'Europe - Sterckx, Pierre (Paris : Beaux Arts Magazine, 2007)
Andre, Carl ; Basquiat, Jean-Michel ; Calder, Alexander ; Close, Chuck ; Riverhead (New York) ; Francis, Sam ; Gober, Robert ; Graham, Dan ; Haring, Keith ; Hill, Gary ; Holzer, Jenny ; Johns, Jasper ; Judd, Donald ; Kelley, Mike ; Kelly, Ellsworth ; de Kooning, Willem ; Koons, Jeff ; Kosuth, Joseph ; LeWitt, Sol ; Lichtenstein, Roy ; Mangold, Robert ; Mapplethorpe, Robert ; McCarthy, Paul ; Mehretu, Julie ; Nauman, Bruce ; Newman, Barnett ; Oldenburg, Claes ; Oursler, Tony ; Paik, Nam June ; Pollock, Jackson ; Rauschenberg, Robert ; Reinhardt, Ad ; Rosenquist, James ; Rothko, Mark ; Ruscha, Edward ; Ryman, Robert ; Segal, George ; Serra, Richard ; Sherman, Cindy ; Smith, Tony ; Smithson, Robert ; Steinberg, Saul ; Stella, Frank ; Turrell, James ; Twombly, Cy ; Viola, Bill ; Warhol, Andy ; Wegman, William ; Wesselman, Tom ; Wool, Christopher
Geboortedata per kunstenaar p. 271-283
Frans
boek
Keywords: New York; U.S.A.; Verenigde Staten van Amerika